Video-assisted versus conventional thoracotomy pneumonectomy: a comparison of perioperative outcomes and short-term measures of convalescence - Liu, Yuanqi; Gao, Yang; Zhang, Huajun; Cheng, Yuanda; Chang, Ruimin; Zhang, Weixing; Zhang, Chunfang (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Background: Pneumonectomy is a proven treatment for lung diseases. We sought to present a comparison between video-assisted video-assisted thoracic surgery pneumonectomy (VATS-P) and conventional thoracotomy pneumonectomy (CP) on perioperative outcomes and short-term measures of convalescence. Methods: A retrospective cohort study was performed to assess perioperative outcomes among patients underwent VATS-P and CP. A total of 32 patients undergoing VATS-P were matched 2:1 about comorbidity, surgical indication, tumour size and lesion location to a previous cohort of 64 patients who underwent CP. Demographic and perioperative data were obtained. Statistical analysis was performed. Results: Mean patient age was 55.4 years for both groups, with equal sex distribution. Pneumonectomy for malignant and benign lesion patients was evaluated individually. For malignant tumour patients, median tumour size was 3.9 cm for both groups. There was no difference between VATS-P and CP cases in transfusion rates (2% vs. 10%, P=0.50), dissected lymph node numbers (11.9 vs. 14.2, P=0.26), dissected lymph node stations (5.0 vs. 4.9, P=0.75), estimated blood loss (226.0 vs. 261.3 mL, P=0.40), complication rate (20.0% vs. 22.5%, P=0.82), postoperative drainage time (5.9 vs. 6.2, P=0.50) or length of hospital stay (7.5 vs. 8.1, P=0.50). Operation time in VATS-P was higher than conventional groups (187.5 vs. 146.3 min, P=0.00) but the mean pain score was significantly less. For benign patients, over 1,000 mL blood losing (1,033.3 vs. 1,233.3 mL, P=0.78) and 180 minutes (186.6 vs. 105.8, P=0.73) OR time was found in both groups. The Length of stay (7.6 vs. 6.3 d, P=0.57), transfusion rates (66.7% vs. 33.3%), complications rates (zero in both group) and length of drainage (6.7 vs. 6.7 d, P=1.0) between two groups are identical. Conclusions: Complete video-assisted video-assisted thoracic surgery (VATS) pneumonectomy is feasible and safe technique and can be recommended as a surgical treatment for lung cancer patients. However, long-term benefits need to be evaluated by further studies and large sample tests.